Fungsi Justice Collaborators Terhadap Kejahatan Terorganisasi Tindak Pidana Narkotika - Silvania Soviana (Jurist-Diction, 2021)
AbstractIllicit drug trafficking is one of the criminal acts that has never subsided in Indonesia because the negative impact is so great and dangerous. As one of the law enforcement officers, the police certainly take part in efforts to eradicate illicit drug trafficking. In carrying out combating organized crime in illicit drug trafficking, the police assume the role of investigator as well as investigator. In carrying out the eradication of organized crime in illicit drug trafficking, the investigator does not merely disclose the crime alone. Investigators are assisted by collaborating witnesses called justice collaborators. The function of the justice collaborators who work together in assisting investigators, donating assistance in the form of providing information, reports, and / or testimonies related to further information about narcotic crimes. The justice collaborators also get legal protection guaranteed by law. Keywords: Illicit Drug Trafficking; Justice Collaborator; Organized Crime.AbstrakTindak pidana Narkotika ialah salah satu dari tindak pidana yang tidak pernah surut eksistensinya di negara Indonesia karena dampak negatif yang disebabkan begitu besar dan membahayakan. Sebagai salah satu aparat penegak hukum, Polisi tentu turut andil dalam upaya pemberantasan tindak pidana Narkotika. Dalam melakukan pemberantasan kejahatan terorganisasi tindak pidana narkotika, Polisi mengemban peran sebagai penyelidik sekaligus penyidik. Dalam melakukan pemberantasan kejahatan teroganisasi tindak pidana narkotika, penyidik tidak semata-mata melakukan pengungkapan tindak pidana tersebut sendirian. Penyidik dibantu oleh saksi pelaku yang bekerjasama yang disebut justice collaborator. Adanya fungsi dari saksi pelaku yang bekerja sama dalam membantu penyidik, menyumbangkan bantuan berupa pemberian informasi, laporan, dan/atau kesaksian terkait keterangan lebih lanjut mengenai tindak pidana narkotika. Saksi yang bekerja sama juga mendapatkan perlindungan hukum yang dijamin oleh undang-undang.Kata Kunci: Kejahatan Terorganisasi; Saksi Yang Bekerja Sama; Tindak Pidana Narkotika.